In vitro effect of Solanum sessiliflorum “cocona” extract on the growth of Helicobacter pylori - Pardo Sandoval, María A (2010)
Was determinated that effect of cocona extract against Helicobacter pylori in culture media, as well as, the effects of the following antibiotics: Amoxicyline, Tetracycline, Claritromycine and Amikacine. The susceptibility for these antybiotics was determined by the method of disk diffusion and the effect of cocona extract against Helicobacter pylori by the method of pouring plate. The Helicobacter pylori strains were obtained of gastric biopsies, the media that were used, were Columbia blood base agar and Mueller Hinton supplemented with 5% sheep blood agar and for reactivating the Helicobacter pylori strains, a specific supplement DENT (Vancomycin 5 mg, trimethropine 2,5 mg, cefsulodin 2,5 mg, amphoterecin B 2,5 mg), the microaerofilic environment was obtained by employing OXOID Campy Gen. The results showed that the cocona extract inhibits the growth of Helicobacter pylori and this effect is superior to the ones obtained by the antibiotics that were used.